African Indigenous Knowledge and the Disciplines - Emeagwali, Gloria. author. aut Link
XIII, 180 p.
Keywords: This text explores the multidisciplinary context of African Indigenous Knowledge Systems from scholars and scholar activists committed to the interrogation, production, articulation, dissemination and general development of endogenous and indigenous modes of intellectual activity and praxis. The work reinforces the demand for the decolonization of the academy and makes the case for a paradigmatic shift in content, subject matter and curriculum in institutions in Africa and elsewhere – with a view to challenging and rejecting disinformation and intellectual servitude. Indigenous intellectual discourses related to diverse disciplines take center stage in this volume with a focus on education, mathematics, medicine, chemistry and engineering in their historical and contemporary context.